ANALYSIS OF COMBINED HEAT AND POWER SYSTEM WITH LOWER OPTIMUM CYCLE PRESSURE RATIO - Dev, Nikhil; Attri, Rajesh (International journal of energy, environment, economics, 2013)
Regenerators are installed with the gas turbine power plants, operating at high pressure ratios and low firing temperatures, to enhance their thermal efficiencies. In general, the enhanced investment for a regenerator installation is returned in twelve to eighteen months. A gas turbine based heat and power cohort systems are on hand with different configurations. Further their performance is affected by design and operating parameters. Complexity of system analysis is increased due to interdependency of components (i.e., air compressor, combustion chamber, gas turbine, regenerator and steam generator) and parameters. Mathematical modeling based upon exergy, energy and mass balance athwart the components is simulated using computer programming tool EES (Engineering Equation Solver). From the results it is found that in case of cogeneration cycle with regenerator optimum cycle pressure ratio is 15 with first law efficiency 85.49% and for cogeneration cycle without regenerator is 36 with efficiency 80.41%.